Effect of BiMeO3 on the Phase Structure, Ferroelectric Stability, and Properties of Lead‐Free Bi0.5(Na0.80K0.20)0.5TiO3 Ceramics. Issue 6 (9th February 2014) - Hao, Jigong; Shen, Bo; Zhai, Jiwei; Chen, Haydn; Zhang, S.
<x xml:space="preserve">Abstract</x> The effects of BiMeO3 (Me = Fe, Sc, Mn, Al) addition on the phase transition and electrical properties of Bi0.5(Na0.80K0.20)0.5TiO3 (BNKT20) lead‐free piezoceramics were systematically investigated. Results showed that addition of BiFeO3 into BNKT20 induces a phase transition from tetragonal–rhombohedral coexisted phases to a tetragonal phase with the observation of enhanced piezoelectric properties (d33 = 150 pC/N for 0.02BiFeO3). BiScO3, BiMnO3, and BiAlO3 substitutions into BNKT20 induce a phase transition from coexistence of ferroelectric tetragonal and rhombohedral to a relaxor pseudocubic with a significant disruption of the long‐range ferroelectric order, and correspondingly adjusts the ferroelectric–relaxor transition point TF–R to room temperature. Accordingly, large accompanying normalized strains of 0.34%–0.36% are obtained near the ferroelectric–relaxor phase boundary, and the mergence of large strain response can be ascribed to a reversible field‐induced ergodic relaxor‐to‐ferroelectric phase transformation. Moreover, our study also revealed that the composition located at the ferroelectric–relaxor phase boundary where the strain response is consistently derivable shifts to a BNKT20‐rich composition as the tolerance factor t of the end‐member BiMeO3 increases, and this relationship is expected to provide a guideline for designing high‐performance (Bi0.5Na0.5)TiO3‐based materials by searching the ferroelectric–relaxor phase boundary.